The relationship between students' self-esteem level and anxiety level in completing theses during the COVID-19 pandemic - Fitri, Amira Melati; Maulana, Muhammad Ali; Fradianto, Ikbal (ProNers, 2024)
Background: The Covid-19 pandemic significantly disrupted educational systems, including higher education, where students faced challenges in completing theses due to remote learning, limited access to resources, and increased anxiety. Self-esteem plays a crucial role in shaping students"™ responses to these challenges.Objective: To analyze the relationship between self-esteem and anxiety levels among students completing theses during the Covid-19 pandemic at Universitas Tanjungpura.Methods: This quantitative study used a descriptive survey design with a cross-sectional approach. Data were collected from 67 students in the Pharmacy and Nursing Programs using online questionnaires, including demographic data, the Rosenberg Self-Esteem Scale (RSE), and the GAD-7 anxiety scale. Bivariate analysis was performed using the Spearman Rank Correlation test.Results: The majority of students exhibited normal self-esteem (88.0%) and mild anxiety levels (46.2%). Although most students managed their anxiety effectively, no significant relationship was found between self-esteem and anxiety levels during thesis completion. Students adapted well to online learning and thesis submission processes during the pandemic, leveraging available resources and time effectively.Conclusion: While no significant relationship was identified between self-esteem and anxiety levels, the study highlights the importance of resilience, emotional support, and adaptive strategies in helping students manage academic challenges during unprecedented circumstances. Further research is recommended to explore additional factors influencing self-esteem and anxiety.